Perceptions and experience of school violence among teachers and learners within a black township in the Sarah Baartman District, Eastern Cape, South Africa - Ndemka, Sibulela (Rhodes University, Faculty of Humanities, Department of Sociology)
In exploring the knowledge/awarness of school violence within the teacher and student school relationship. The principal objective of the study was to investigate the perceptions and experiences of school violence among teachers and learners by reference to a public high school in a historically black African, working class township in the Sarah Baartman District Municipality, Eastern Cape Province, South Africa. The high school was chosen for its geographical location within the community and relative nature of shared stories of violence within the surrounding vicinity. The conceptual, theoretical, and analytical frameworks underpinning this study is social constructionism theory, expanding from the theoretical claim that violence is socially constructed through the process of socialisation and institutionalization. The study reviewed relavant literature on violence in South African schools highlighting the relationship of school violence to current social and educational challenges and crises and the impact that school violence has on learners, teachers, and communities. The research methodology employed is qualitative and evidence was derived through semi-structured in-depth interviews. A sample male and female teachers and learners were recruited through networking. The researcher recruited participants outside the school and through participant referrals to uncover intricacies of school violence drawing on relevant literature in relation to the dynamics of this social and institutional problem. Data was analysed and thematically presented in line with the research objectives. The study findings imply that school violence is complex and gendered. Arguing that cultural, socio-economic, family, community, and social interpersonal factors account for school violence in South Africa. Male teachers and students mostly bieng the victims and perpetrators, implicating this behaviour to a culture of toxic masculinity and shared complicities as contributing factors to school violence. In addition, the study found that the change in status and expectations of boys who return from initiation sometimes provoked violence between initiated learners and adults who did not accord them the respect expected post-initiation.
Keywords: School violence -- South Africa -- Eastern Cape; Teachers -- South Africa -- Eastern Cape Attitudes; High school students -- South Africa -- Eastern Cape Attitudes; High school students Conduct of life; High school students Economic conditions; High school students Social conditions; Social constructionism -- South Africa -- Eastern Cape